DATABUSTING FOR SCHOOLS : HOW TO USE AND INTERPRET EDUCATION DATA - Selfridge, Richard; Clark, James (London : SAGE Publications, 2018)
Data in education is increasingly important but, despite their best efforts, teachers and educators frequently struggle to understand the core principles of data use and interpretation. This book will help you understand the use of statistics in education, and show you how to use data effectively in your classroom and school. As a guide to data, the book explores variables and how they are manipulated. It explains both descriptive statistics, which aim to explain the past, and inferential statistics which try to make predictions about the future and the wider population. It also explores how data has been used in the world of educational research, and examines criticisms of using data to summarize children$1 (Bs education.s
Includes bibliographical references and index.
Keywords: Education -- Data processing; Big data; Educational statistics